A Rare Complication of Umbilical Vein Catheterization: TPNoma: US, X-ray, and MRI Findings - Sari, Lutfullah; Oran, Zeynep; Ali Gültekin, Mehmet; Sharifov, Rasul; Toprak, Hüseyin (Current Medical Imaging, 2023)
Background: Umbilical vein catheterization (UVC) is an early venous access route in newborns and is frequently used for delivering total parenteral nutrition (TPN) and medications. Vascular, hepatic parenchymal, and infectious complications of UVC can be seen rarely. Objective: We present preterm neonates' X-ray, US, and MRI findings with parenchymal TPN extravasation and portal vein thrombosis. Our case was the first case about MRI findings of TPNoma. Case Presentation: A 30 week female with a birth weight of 1340 g was born via Cesarean section. Due to the diagnosis of transient tachypnea of the newborn and prematurity, the infant was hospitalized in the neonatal intensive care unit. On the first day of hospitalization, UVC was inserted and TPN with 20% lipid content was started. After 10 days, UVC was removed and TPN treatment was continued with a piccline catheter. Abdominal US and portal venous Doppler examination was applied to the patient whose general condition deteriorated on the 12th day. US and Doppler revealed a lesion of 17x17x18mm in size with lobulated contour, hyperechoic heterogeneous internal structure, and no central or peripheral blood supply was observed in the left lobe of the liver. Moreover, a filling defect compatible with a thrombus was observed in the proximal part of the left portal vein. An abdominal MRI was performed to characterize this liver lesion. Axial T1 weighted and T2- weighted images showed a heterogeneous hyperintense lesion without contrast enhancement. Axial fat saturation T1-weighted and out of phase T1-weighted images showed a reduction in signal intensity. US and MRI examinations showed that the thrombosed umbilical vein ended superior to the lesion. In the differential diagnoses, fat-containing lesions such as lipoma-teratoma and fat-containing collection secondary to extravasation of TPN treatment via UVC were thought. Conclusion: In the differential diagnosis of liver localized lesions in newborns, UVC-related liver injury should be considered and the localization of the catheter tip should be checked. In case of the doubt based on US and X-ray findings, presence of fat on MRI could be diagnosed. Serious complications should be avoided with catheter revision or removal.
Keywords: TPNoma